The Effect of Task Based Language Teaching Method on English Speaking Skills at SMP Negeri 06 Kaur - Gina Anggilia; Ferri Susanto; Anita Anita (The Future of Education Journal, 2025)
Speaking skills are crucial to learning English. However, many students still struggle to speak fluently due to anxiety, lack of confidence, and fear of making mistakes. This study aims to assess how effectively the Task-Based Language Teaching (TBLT) method can enhance the speaking abilities of seventh-grade students at SMP Negeri 06 Kaur. The research employed a quantitative, quasi-experimental design with two classes: VII-A as the experimental group and VII-B as the control group. The primary data collection tool was a speaking test, and analysis was conducted using ANOVA in SPSS version 26. The findings revealed that the experimental group showed greater improvement in speaking skills than the control group. The experimental group's pre-test scores, initially ranging from 16 to 58, increased to 50-83 in the post-test, with an average score of 60.03. In contrast, the control group's scores only rose from 8 to 58 in the pre-test to 29 to 66 in the post-test, averaging 46.34. The ANOVA results indicated an F value of 49.014, which exceeds the F table value of 4.00, and a Partial Eta Squared of 44.2%, confirming that TBLT significantly enhances students' speaking skills. Therefore, it can be concluded that the TBLT approach effectively improves the speaking skills of seventh-grade students at SMP Negeri 06 Kaur.